ANALISIS FAKTOR YANG MEMPENGARUHI RENDAHNYA PARTISIPASI LANSIA DALAM PEMANFAATAN POSYANDU LANSIA DI PUSKESMAS PAUH KEMBAR KABUPATEN PADANG PARIAMAN TAHUN 2019 - Eva Susanti; Nursal Asbiran; Nur Hayati (HUMAN CARE JOURNAL, 2020)
Elderly Integrated Service Post (Posyandu) is one of the efforts to improve the health status and quality of health care for the elderly in the community, happy and efficient for the family and communication between the elderly. This study aims to determine the factors that influence the low participation of the elderly in the use of Posyandu Elderly in Pauh Kembar Health Center, Padang Pariaman Regency in 2019. The research method used is a cross sectional approach. The study was conducted at the Pauh Kembar Health Center in Padang Pariaman Regency from May 14 to June 31, 2019. The analysis found that there was a significant relationship between work with a p value of 0,000 and OR = 6.3. p value of elderly motivation with p value 0.003 and OR = 3.661, cadre role with p value 0.041 and OR = 2,464, distance of home from Posyandu with p value 0,000 and OR = 7,837, and health condition p value 0.022 and OR = 2,981 with participation elderly to Posyandu Elderly. It can be concluded that the distance between home and Posyandu has the greatest risk among other variables. It is suggested the need for holistic and integrated efforts to utilize the posyandu for the elderly in order to improve the health status of the elderly.